2017
DOI: 10.1021/acs.joc.6b02642
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand-Dissociation-Involved Mechanism in Amide Formation of Monofluoroacylboronates with Hydroxylamines

Abstract: Acylborons, as a growing class of boron reagents, were successfully applied to amide ligation and showed potential in chemoselective bioconjugation reactions in recent years. In this manuscript, a density functional theory (DFT) study was performed to investigate the mechanism of the amide formation between monofluoroacylboronates and hydroxylamines. An updated pathway was clarified herein, including water-assisted hemiaminal formation, pyridine ligand dissociation, elimination via a six-membered-ring transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…23,24 Recently, the M06 method has often been utilized to investigate processes involving BH and hydroxylamine. 14,[25][26][27][28] The geometries of each species involved were fully optimized at the level of 6-31+g(d,p) in the gas phase. Frequency analyses were conducted with the same basis set to confirm that the optimized structures were ground states without imaginary frequency.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…23,24 Recently, the M06 method has often been utilized to investigate processes involving BH and hydroxylamine. 14,[25][26][27][28] The geometries of each species involved were fully optimized at the level of 6-31+g(d,p) in the gas phase. Frequency analyses were conducted with the same basis set to confirm that the optimized structures were ground states without imaginary frequency.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…Subsequent elimination via a sixmembered-ring transition state, and final water-assisted tautomerization generates the corresponding amide (36). 37 The Please do not adjust margins Please do not adjust margins utility of this ligation strategy was emphasized through the development of a traceless, templated amide forming process that proceeds at low micromolar concentrations in aqueous media. 38 Bode and coworkers also demonstrated an amide formation process between primary amines or amides with KATs (4) promoted by simple chlorinating agents, such as 1,3-dichloro-5,5-dimethylhydantoin (DCH) and 1,3,5-trichloroisocyanuric acid (TCCA) (Scheme 10a).…”
Section: Boronmentioning
confidence: 99%
“…Subsequent elimination via a six-membered-ring transition state, and final water-assisted tautomerization generates the corresponding amide ( 36 ). 37 The utility of this ligation strategy was emphasized through the development of a traceless, templated amide forming process that proceeds at low micromolar concentrations in aqueous media. 38 …”
Section: Boronmentioning
confidence: 99%
“…Given our interest in the amide bond formation and Pd-catalyzed cross-couplings with CO, we also conducted a DFT study to investigate the HAC reactions reported by Huang . Different mechanistic insights were discovered for the Pd-catalyzed couplings of mono-substituted alkenes, CO, and NH 4 Cl with P­( t Bu) 3 and xantphos as ligands.…”
Section: Introductionmentioning
confidence: 99%